Image-guided high-dose-rate interstitial brachytherapy for recurrent rectal cancer after salvage surgery: a case report - Yanping, Bei; Murakami, Naoya; Shima, Satoshi; Takahashi, Kana; Inaba, Koji; Okuma, Kae; Igaki, Hiroshi; Nakayama, Yuko; Itami, Jun (Journal of Contemporary Brachytherapy, 2019)
Treatment options for patients with recurrent rectal cancer in pelvis represent a significant challenge because the balance of efficiency and toxicity needs to be pursued. This case report illustrates a treatment effect of image-guided high-dose-rate interstitial brachytherapy (HDR-ISBT) for locally relapsed rectal cancer after salvage surgery. A 61-year-old male who underwent laparoscopic high anterior resection (LAP-HAR) with D3 lymph node dissection as a primary treatment for rectal cancer (pT3N0M0, well-differentiated adenocarcinoma) had relapsed locally 8 months after initial surgery, for which he underwent salvage abdominal perineal resection (APR), followed by adjuvant 8 cycles of XELOX (capecitabine and oxaliplatin) chemotherapy. He developed pelvic recurrence 1 year after the second surgery. Image-guided HDR-ISBT was performed (30 Gy/5 fractions/3 days) followed by external beam radiation therapy with 39.6 Gy in 22 fractions. There were no severe complications related to salvage radiotherapy. CEA was decreased from 24.5 ng/ml to 0.7 ng/ml, 4 months after the salvage radiotherapy. Complete response was noted on follow-up MRIs done on 2, 5, 8, and 14 months after the treatment. Hence, HDR-ISBT appears to be effective for locally recurrent rectal cancer even after salvage surgery.